2021
DOI: 10.1111/jac.12495
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress lowers yields, alters nutrient uptake and changes seed quality in quinoa grown under Mediterranean field conditions

Abstract: The global expansion of quinoa (Chenopodium quinoa Willd.) cultivation has been related to the nutritional properties of its seeds and the ability of this crop to cope with stress. However, research works evaluating the agronomic impact of quinoa cultivation out of the Andean region are still limited, especially under Mediterranean field conditions. In this work, the agronomic performance, seed composition and nutrient uptake (NU) of five quinoa varieties were analysed in two consecutive years (2017)(2018) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
61
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 48 publications
8
61
2
Order By: Relevance
“…Besides, the relationship between yield and nutritional quality-related traits such as the protein content, is influenced by the genotype and the environment, in quinoa and other crops (Caballero et al, 2015;Halford et al, 2015;Curti et al, 2018). For this reason, a deeper analysis of yield influence in seed quality traits was performed (Table 4) and an important negative effect of yield on protein content was found, agreeing with the trade-off described by Curti et al (2018) for winter sowing and with other similar findings in quinoa (De Santis et al, 2016;Präger et al, 2018;Reguera et al, 2018;Prieto et al, 2021) and other crops, including cereals (Simmonds, 1995;Rondanini et al, 2019). Nonetheless, both, yield and protein content, have also been shown to increase simultaneously when fertilizing with N (Caballero et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Besides, the relationship between yield and nutritional quality-related traits such as the protein content, is influenced by the genotype and the environment, in quinoa and other crops (Caballero et al, 2015;Halford et al, 2015;Curti et al, 2018). For this reason, a deeper analysis of yield influence in seed quality traits was performed (Table 4) and an important negative effect of yield on protein content was found, agreeing with the trade-off described by Curti et al (2018) for winter sowing and with other similar findings in quinoa (De Santis et al, 2016;Präger et al, 2018;Reguera et al, 2018;Prieto et al, 2021) and other crops, including cereals (Simmonds, 1995;Rondanini et al, 2019). Nonetheless, both, yield and protein content, have also been shown to increase simultaneously when fertilizing with N (Caballero et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…While the evidences presented by Miranda et al (2012) suggest a strong influence of the genotype in the amino acids contents, the studies performed by Reguera et al (2018) and Prieto et al (2021) support the hypothesis that environmental factors can influence the protein content of quinoa seeds. Reguera et al (2018) found differences in protein quantity among seeds harvested in different countries but not among cultivars in a certain location, while Prieto et al (2021) showed an important increase in quinoa protein content when the crop underwent heat stress. In the present study, there is a strong influence in both protein and amino acids contents by the year of cultivation, being 2018 the growing season with higher contents except for cysteine and tryptophan (Figure 5 and Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Nonetheless, further analysis should be performed to determine the exact impact of heat stress on the vegetative growth and its influence on straw yield, particularly in quinoa. It should be noted that the high straw yield achieved by Marisma (2.8 t ha −1 , on average), especially in 2018 (3.9 t ha −1 ), was well correlated with a higher seed yield, as previously reported [36], which is interesting from an agronomical perspective because seed yield penalties should be avoided. Intriguingly, the two-year average straw yield (1.9 t ha −1 ) achieved in this work was lower than those previously reported for Mediterranean field conditions (3.0 t ha −1 for Titicaca; 7.4 t ha −1 for Regalona) [37], and similar to those obtained by Asher et al (2020), although at the bottom of the range (0.5-9.1 t ha −1 ).…”
Section: Discussionsupporting
confidence: 76%
“…Overall, the results here presented show that Marisma is the variety with the best cultivation potential in terms of straw yield for this particular area (Southwestern Spain), despite suffering important yield penalties linked to the elevated temperatures suffered in 2017 [36]. Furthermore, the straw composition analysis performed shows that quinoa straw is a valuable resource for animal feed, biofuel, or biomaterial production.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation